Beyond digital platforms: Gamified skill development in real-world scenarios and environmental variables - Mohamad Ahmad Saleem Khasawneh (International Journal of Data and Network Science, 2024)
The goal of this study is to investigate the efficacy of gamified training programs and the influence of contextual variables on skill learning in the specific context of Saudi Arabia. Current research examines the impact of cultural and socioeconomic variables on the efficacy of gamification as a motivating tool. Moreover, it explores the use of real-world situations in skill-development initiatives, paying special attention to how such programs mesh with the aims of Saudi Vision 2030. The goal of this lofty strategy is to develop a knowledgeable and talented labor force and stimulate economic growth. Incorporating quantitative analysis helps to reveal a statistically significant and positive association between involvement and the enhancement of abilities, lending credence to the efficacy of gamified techniques. Extensive studies have also shown that a wide range of external influences have a major impact on the educational setting. Culture, social status, technical progress, and level of education are just a few examples of the many characteristics that fall under this category. They all contribute significantly to the educational setting. To effectively bridge the gap between academic ideas and their practical manifestations, it is crucial to include real-world experiences. Policymakers, educators, and organizations working to improve skill development within Saudi Arabia's specific context may gain much-needed insights from the aforementioned results.